Long‐term experience using CNI‐free immunosuppression in selected paediatric heart transplant recipients. (18th August 2021) - Rosenthal, Lisa‐Maria; Nordmeyer, Johannes; Kramer, Peter; Danne, Friederike; Pfitzer, Constanze; Berger, Felix; Schmitt, Katharina Rose Luise; Schubert, Stephan
Abstract: Background: CNI‐free immunosuppression with conversion to mTORi‐based immunosuppression has been demonstrated to reduce CNI‐toxicity and to exhibit anti‐proliferative properties. However, the experience of CNI‐free immunosuppression in paediatric heart transplantation is limited. Methods: A retrospective analysis was conducted of 129 paediatric heart transplants performed between 1997 and 2015. Fifteen patients with clinically indicated conversion from CNI‐based to CNI‐free immunosuppression were identified. Survival data, rejection episodes, renal function, post‐transplantation lymphoproliferative disorder and CAV, including examination with OCT were analysed. Results: Immunosuppression conversion was successful in all patients. Fourteen of 15 patients (93%) are currently living with good graft function. Median post‐transplant survival was 15 years (range, 5–23 years), and median follow‐up since conversion was 6 years (range, 1–11 years). Mild (grade 1R) ACR was present in three patients after discontinuation of CNIs. The recovery of renal function with a significant increase in eGFR was observed at 1 and 3 years after conversion. No patient had angiographic signs of macroscopic CAV according to the current ISHLT classification; however, OCT showed the signs of angiographically silent CAV in all patients. CAV did not progress in any patient, implying CAV was stabilised by mTORi‐based CNI‐free immunosuppression. Conclusions: CNI‐free immunosuppression based on mTORis is a safe and appropriate strategy for maintenance therapy in selected paediatric patients, significantly improves renal function and stabilises CAV. OCT revealed early development of angiographically silent CAV.